Techniques of Social Influence The psychology of gaining compliance - Dolinski, Dariusz (Taylor & Francis, 2015)
This accessible text provides an overview of different social influence techniques, which people use in order to make others meet various requests, suggestions and commands. Author Dariusz Dolinski does not merely describe these techniques, but also explores the research behind them: how do we know that they work, and under what conditions are they more or less likely to be effective. A perfect introduction for psychology graduates and undergraduates studying social influence and persuasion, this original text will also appeal to scholars and students in neighboring disciplines, as well as interested practitioners in the field of sales and marketing.